2014
DOI: 10.5535/arm.2014.38.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Traumatic Pneumorrhachis Accompanied by Paraparesis

Abstract: Pneumorrhachis, caused by intraspinal air, is an exceptional but important radiographic finding that is accompanied by different etiologies. Pneumorrhachis, by itself, is usually asymptomatic and gets reabsorbed spontaneously. Therefore, the patients with pneumorrhachis are mostly managed conservatively. We encountered a unique case of atypical traumatic pneumorrhachis accompanied by paraparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…It can be primary or secondary; epidural or subarachnoid; iatrogenic, traumatic, or nontraumatic in terms of the source, location, and etiology, respectively. 7,10 Newbold et al 11 considered pneumorrhachis as a marker of fracture of the skull base and reported one case of traumatic cervical pneumorrhachis in 1987. Since 1987, many cases have been reported in the literature (Table 1).…”
Section: Journalmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be primary or secondary; epidural or subarachnoid; iatrogenic, traumatic, or nontraumatic in terms of the source, location, and etiology, respectively. 7,10 Newbold et al 11 considered pneumorrhachis as a marker of fracture of the skull base and reported one case of traumatic cervical pneumorrhachis in 1987. Since 1987, many cases have been reported in the literature (Table 1).…”
Section: Journalmentioning
confidence: 99%
“…Dural tear creates a communication pathway for air into the subarachnoid space from the extracalvarial or extra-spinal air. 10,11 In 2010, Chaichana et al 3 reported traumatic pneumorrhachis in a 35-year-old male patient after RTA: he was fully conscious and GCS was 15 but had otorrhea from the left side, left facial deficit, and decreasing hearing on the left side. Thus, the authors concluded that the evidence of severe trauma is the leading risk factor in the occurrence of pneumorrhachis.…”
Section: Journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Nontraumatic PNR may be caused by vertebral degeneration, malignancy, radiotherapy, and gas-producing infections. Traumatic PNR may be caused by head injuries; spinal trauma; or cervical, thoracic, or abdominopelvic injuries [1,2]. Traumatic cervical PNR frequently is accompanied by anterior fossa injury.…”
mentioning
confidence: 99%
“…(7) PR secondary to trauma is uncommon in the literature, and may occur due to causes such as: traumatic brain injury, cervical, thoracic, abdominal, and pelvic injuries and may result from penetrating spinal cord injuries by a firearm or sharpener. (3,7,9) Air can enter the spinal canal directly or indirectly, the first mainly of traumatic or penetrating origin; And the second by dissection of the soft paraspinals by a unidirectional valve mechanism until reaching the spinal canal. (4) Generally, this air within the cord does not migrate and is spontaneously reabsorbed into the bloodstream for several days without relapse.…”
Section: Case Reportmentioning
confidence: 99%